The feasibility in estimating pulmonary vascular resistance by cardiovascular magnetic resonance in pulmonary hypertension: A systematic review and meta-analysis. Issue 114 (May 2019) - Chen, Hang; Xiang, Bo; Zeng, Jian; Luo, Hechuan; Yang, Quan
Abstract: Purpose: Cardiac magnetic resonance (CMR) is a substitute technique for noninvasively assessing pulmonary hemodynamics. Some preliminary studies have shown that CMR has the potential to quantify pulmonary vascular resistance (PVR). However, the evaluative value has not been well established. The purpose of the systematic review is to assess the feasibility of CMR in the measurement of PVR in patients with pulmonary hypertension (PH). Methods: Studies were retrieved from multiple databases. Methodological evaluation of CMR and right heart catheterization (RHC) in estimating PVR were obtained from included studies. The Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2) tool was used to assess the quality of studies. The results of comparisons of continuous variables are reported as weighted mean difference (WMD), together with the corresponding 95% confidence intervals (CIs). Summary correlation coefficient (r) values were extracted from each study, and 95% CIs were calculated after Fisher's z transformation. Sensitivity analysis was conducted to investigate potential heterogeneity. Results: A total of 15 studies were included in the systematic review, and 6 of these studies were included in the meta-analysis. The pooled WMD with fixed-effects analysis revealed no statistical significance between PVR-CMR and PVR-RHC in patients with PH (WMD = 0.278 WU; 95% CI: −0.415 to 0.972; p = 0.431). The pooled r value for all studies was 0.85 (95% CI: 0.81, 0.89), and notable heterogeneity was evident. The pooled r value after the exclusion of one heterogeneous article was 0.81 (95% CI: 0.74, 0.87) and was not significantly heterogeneous. Conclusions: CMR and RHC have good consistency in the testing of PVR in the meta-analysis. The systematic review shows that completely noninvasive evaluation of PVR with CMR in patients with pH is feasible.